Types of errors in Raven tests in a population with Down syndrome: An online assessment - Barrón Martínez, Julia Beatriz; Salvador Cruz, Judith (ELSEVIER, 2025)
The objective of this study was to describe the types of visuoperceptual errors on Raven tests in a sample of Mexican people with Down syndrome (DS), and to explore whether these errors were related to mental age (MA) or chronological age (CA). Participants included 50 people with DS, with a mean CA of 19.47 years and a mean MA of 7.40 years. The Raven Colored Progressive Matrices test was used to obtain the MA and also to analyze four types of errors: 1) difference, 2) figure repetition, 3) inadequate individuation, and 4) incomplete correlates. The study was carried out online due to the COVID-19 pandemic. Participants made an average of 22.84 errors on a total of 36 items. No predominance was found of any of the four types of errors. However, MA was negatively correlated with three error types. Because there are similar proportions of the four errors, the results do not allow us to define a specific perceptual deficit profile; errors on the test could be the result of general difficulties in the organization of perceptual information. Future studies could investigate whether this pattern of results is related to cognitive abilities such as working memory or executive functions.
1. The objective of this study was to identify the types of errors made on the Raven (divided into difference, figure repetition, inadequate individuation, and incomplete correlates. Although no statistically significant differences were found between the types of errors, the most common was figure repetition. 2. This is the first study in a Mexican population with Down syndrome that analyzes the types of errors made on the Raven test, in order to understand the types of perceptual information that present difficulty in processing. 3. The results from this and future studies could form the basis of educational intervention programs for people with Down syndrome, focused on enhancing the perceptual abilities represented by each of the four types of errors (for example, patterns, analogies, distortions, irrelevancies, or rotation of geometric or non-geometric elements) in order to achieve better cognitive performance in these areas.
Keywords: Down Syndrome; raven tests; perceptual abilities; online assessment